Do legal prescriptions ensure public accountability? Insights and lessons from local governments in Bangladesh. Issue 1 (2nd January 2018) - Ahsan, A. H. M. Kamrul; Chowdhury, Mst. Shuvra; Panday, Pranab
Abstract : This article, which is based on qualitative research, addresses legally-prescribed mechanisms of public accountability and the extent of their use and effect at the lowest level of local government in Bangladesh. The findings are that, while various mechanisms have been established, they have not been effective in holding local representatives to account for what they do and achieve. The main reasons for this have been the unresponsiveness of the representatives, as well as the inability and/or reluctance of local residents to exercise their formal rights of participation and control. These matters pose fundamental challenges which must be the focus of comprehensive change and reform aimed at significantly strengthening local governance and democracy.